Effect Of Machining Parameters On Surface Roughness In Edge Trimming Of Carbon Fiber Reinforced Plastics (CFRP) - Sundi, Syahrul Azwan; Raja Abdullah, Raja Izamshah; Kasim, Mohd Shahir (Japanese Society of Tribologists, 2020)
The main aim of this research was to investigate the effect of machining parameters towards surface quality during edge trimming process on a specific CFRP material. There were two variation of machining parameters focused in this work namely spindle speed (N) and feed rate (Vf). The CFRP panel is measured 3.25 mm in thickness and the type of fabric was unidirectional (UD). It has 28 number of plies in total and were arranged multi-directional. Router or burr tool geometry made of uncoated tungsten carbide with a diameter of 6.35 mm was used to perform the edge trimming process. Surface roughness measurement was taken using Mitutoyo Surftest SJ-410. Furthermore, optical microscope Nikon MM-800 is utilized to further observe the trimmed surfaces. The result reveals that the smallest value of the surface roughness (1.31 µm) is obtained by Run 8 (R8) which the spindle speed, N applied was 2506 rpm and feed rate, Vf at 376 mm/min. Meanwhile, the highest surface roughness value (12.62 µm) exhibited by the R9 which had the highest setting of spindle speed, N 7518 rpm and the highest feed rate, Vf 1128 mm/min. The result is supported by the observation of trimmed surface through optical microscopy which clearly exhibits uncut fibers and matrix degradation condition. Details results elaborated and discussed further in this paper.